Rekonstruksi Ganti Kerugian dan Rehabilitasi dalam Hukum Acara Pidana Indonesia Perspektif Keadilan Islam - Harmianto Harmianto; Titi Sulastry S; Irna Rufaida Arman; Sukmawati Sukmawati; Nurelita Surya; Asreni Aziz (Universitas Islam Darud Da'wah Wal-Irsyad A.G.H. Abdurrahman Ambo Dalle, 2025)
Compensation and rehabilitation are important instruments in criminal procedural law because they function to restore the rights of individuals harmed by unlawful arrest, detention, prosecution, examination, or other legal actions. The main issue examined in this article is how compensation and rehabilitation regulations can guarantee the restoration of the dignity of victims of misprocesses, and what obstacles prevent these rights from being optimally implemented. This research uses a normative juridical method with a statutory, conceptual, and case-based approach. Legal materials are analyzed through a review of the 1981 Criminal Procedure Code, Government Regulation No. 92 of 2015, Law No. 48 of 2009, Law No. 39 of 1999, Constitutional Court Decision No. 21/PUU-XII/2014, and updates in Law No. 20 of 2025 concerning the Criminal Procedure Code. The results of the study indicate that compensation and rehabilitation are not sufficiently understood as administrative procedures, but must be viewed as a form of state responsibility to correct errors in the criminal process. The main obstacles lie in low public awareness, procedures that are not always easily accessible, difficulties in proving losses, limited reputation restoration, and weak accountability of law enforcement officials. This article emphasizes the need for a simpler, more transparent